2002
DOI: 10.1063/1.1524313
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric polarization in stretched piezo- and pyroelectric poly(vinylidene fluoride-hexafluoropropylene) copolymer films

Abstract: After suitable preparation, films of poly(vinylidene fluoride-hexafluoropropylene) [P(VDF-HFP)] show strong piezo- and pyroelectric effects. We investigated the polarization buildup in stretched P(VDF-HFP) copolymer films, cast from a dimethylsulfoxide/acetone solution. The films were poled under varying or constant electric fields. We observed a hysteresis of the polarization as a function of the electric field during poling of the stretched P(VDF-HFP) copolymer films with varying electric fields. From the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Bulky side groups can be introduced though the formation of copolymers containing PVDF, TrFE, and either chloride containing monomers such as cholorofluoroethylene (CFE) [102,105] and chlorotrifluoroethylene (CTFE) [106,107] or hexafluoropropylene (HFP). [108][109][110] The actuation mechanism is essentially the same as for ferroelectric polymers; a transition between paraelectric and ferroelectric phases is induced by the application of a high electric field as represented in Figure 4. Recent work by Bao et al [111] has shown that P(VDF-TrFE) synthesized via reductive dechlorination from P(VDF-CTFE) exhibits ferroelectric relaxor behavior at high temperature (%100 8C) with a melting point near 200 8C.…”
Section: Relaxor Ferroelectric Polymersmentioning
confidence: 99%
“…Bulky side groups can be introduced though the formation of copolymers containing PVDF, TrFE, and either chloride containing monomers such as cholorofluoroethylene (CFE) [102,105] and chlorotrifluoroethylene (CTFE) [106,107] or hexafluoropropylene (HFP). [108][109][110] The actuation mechanism is essentially the same as for ferroelectric polymers; a transition between paraelectric and ferroelectric phases is induced by the application of a high electric field as represented in Figure 4. Recent work by Bao et al [111] has shown that P(VDF-TrFE) synthesized via reductive dechlorination from P(VDF-CTFE) exhibits ferroelectric relaxor behavior at high temperature (%100 8C) with a melting point near 200 8C.…”
Section: Relaxor Ferroelectric Polymersmentioning
confidence: 99%
“…The investigation of these composites has been performed to determine if they represent piezoelectric reactives. Fluorel™ FC-2175 (chemically equivalent to Viton™), a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP), was chosen to be used because it exhibits ferroelectric properties without the need of poling or stretching of the material [3]. Dyneon TM THV220A, a terpolymer of tetrafluoroethylene (TrFE), hexafluoropropylene (HFP), and vinylidene fluoride (VDF) was also used due to its potential to store energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…The sample should be monitored for contaminants as the charges may get injected into the material at high electric and thermal fields [29]. Both constant and varying electric fields can be applied to the sample during electrode poling [30,31]. A constant electric field is held on the sample from 10-30 minutes up to 2 hours [32][33][34].…”
mentioning
confidence: 99%